Digital Currency in Indonesia (Prospects and Challenges in Inclusive Financial Reviews) - Syamsu Alam; Muh. Jamil; Andi Syamsir (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
Who controls global finance? Digitalization is a necessity that will disrupt every area of human life. Money is like 'blood' in the economy. If the currency is disrupted then all areas of human life are also disrupted. Private versions of cryptocurrencies have disrupted the global financial system controlled by Central Banks. Central Bank Digital Currency (CBDC) is the currency version of the Central Bank. Using primary data and reference studies on Digital Currency. Several empirical challenges and opportunities in adopting digital currencies such as increasing the effectiveness, efficiency, and accessibility of individuals to financial service facilities. The right, reliable and trusted Digital Currency model can increase the utility of transactions for individuals and the economy as a whole. Some of the main challenges of digital infrastructure, security systems, Integration, Innovation of new services, disintermediation, transparency and efficiency. The ability to overcome these challenges can increase financial sector.